Legal Politics and Fulfillment of Citizens’ Basic Rights in Indonesia’s Democratic State - Otong Syuhada; Ikmal Hisham; Nazli Ismail Nawang (Sekolah Tinggi Hukum Bandung, 2024)
The purpose of this study is to analyze the state’s responsibility in fulfilling the fundamental rights of every citizen. It is a descriptive-normative research, utilizing both statute and policy approaches. The data for this study were collected using library research methods and will be analyzed through qualitative techniques. The study found that the fulfillment of fundamental rights such as education (8.69 million) and poverty alleviation (9.57% or 26.36 million). However, the fulfillment of fundamental right to employment has not been optimally realized, reaching only (8.42 million). Therefore, the government must take strategic measures to address these issues through more concrete legal politics that directly cater to the interests of all layers of society.